2010
DOI: 10.1371/journal.pmed.1000317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Based Maternal Health Workers on Coverage of Essential Maternal Health Interventions among Internally Displaced Communities in Eastern Burma: The MOM Project

Abstract: Mullany and colleagues report outcomes from a project involving delivery of community-based maternal health services in eastern Burma, and report substantial increases in coverage of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 13 publications
4
107
0
1
Order By: Relevance
“…Pregnant women and midwives posited that women would make improved dietary choices, within their social constraints, if they were provided with appropriate information regarding nutrition. However, the reach of clinic-based care during pregnancy is far from comprehensive in this border region, with limitations in clinic-based programming for maternal nutrition [24,54,55]. Awareness-raising at a community level should be considered to reach younger women whose diets may be tied to the choices of older members of the household.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and midwives posited that women would make improved dietary choices, within their social constraints, if they were provided with appropriate information regarding nutrition. However, the reach of clinic-based care during pregnancy is far from comprehensive in this border region, with limitations in clinic-based programming for maternal nutrition [24,54,55]. Awareness-raising at a community level should be considered to reach younger women whose diets may be tied to the choices of older members of the household.…”
Section: Discussionmentioning
confidence: 99%
“…Longlasting Allen 1998 41 Benet 2006 42 Kaushik 1992 88 Nosten 1991 48 Poesproprodjo 2008 37 Singh 1999 29 Brabin 1990 Primip 89 Brabin 1990 Multip 89 Hamer 2009 Review insecticide-treated bednets are distributed in all countries, 14 but reports in the past 3 years have shown low availability or use by pregnant women. 26,34,128 Case management is available everywhere, but in reality malaria smears are obtained from pregnant women only when fever or other malarial symptoms are present and these symptoms are often not checked by health workers. 128 Papua New Guinea is the only country with a policy for intermittent preventive treatment in pregnancy.…”
Section: Preventionmentioning
confidence: 99%
“…They were identified as having significant functions in delivering the maternal health information to the women in communities and to support families during pregnancy and labour. As described in the background, Bhutta, Soofi, Cousens, Mohammad, Memon & Ali (2011);Mullany, et al (2010) and Prost, et al, (2013) provided evidence on the positive impact of the involvement of cadres in increasing the use of maternal health care in developing countries. Further studies in the same documents concluded that as members of the society, the community health workers were creating supportive environments for maternal women to learn; information was delivered casually in the community routine and through daily communications.…”
Section: Village Midwives' Perspectives On the Factors Influencing Mamentioning
confidence: 99%
“…Several programs have been implemented to increase the community awareness of maternal health. The main factor that emerges from the literature is the effectiveness of community involvement especially from women's groups towards increasing maternal health awareness (Bhutta, Soofi, Cousens, Mohammad, Memon & Ali, 2011;Mullany, et al, 2010;Prost, et al, 2013).…”
mentioning
confidence: 99%